The importance of external costs for assessing the potential of trams and trains for urban freight distribution. (September 2017) - De Langhe, Katrien
Abstract: As a solution for increasing urban freight distribution issues, such as rising vehicle movements, more environment-friendly transport modes including rail could be an option. So far, investigation within this domain has been confined primarily to applying (social) cost-benefit analyses to specific cases. These existing (social) cost-benefit analyses show the importance of external costs in the profitability calculations of urban rail freight initiatives. Therefore, accurate and appropriate external cost data are crucial for the robustness of a social cost-benefit framework. This paper identifies firstly the external cost elements related to the use of trams and trains for urban freight distribution. Secondly, a range of common external cost values is provided for Belgian and Flemish urban areas. A minimum and maximum value is determined for each external cost, when available data allowed this. In further research, these values will be used as input for a generic social cost-benefit framework to assess the potential of trains and trams for urban freight distribution. Highlights: External costs in an urban rail freight context are examined. External cost values for LGVs, trains and trams are provided. The external cost values show the potential for policy makers to favour certain modes. Vehicle manufacturers and energy producers can derive the need for green technologies.